ECM-mimicking hydrogel models of human adipose tissue identify deregulated lipid metabolism in the prostate cancer-adipocyte crosstalk under antiandrogen therapy - Agathe Bessot; Joan Röhl; Maria Emmerich; Anton Klotz; Akhilandeshwari Ravichandran; Christoph Meinert; David Waugh; Jacqui McGovern; Jenni Gunter; Nathalie Bock (Materials Today Bio)
Antiandrogen therapies are effectively used to treat advanced prostate cancer, but eventually cancer adaptation drives unresolved metastatic castration-resistant prostate cancer (mCRPC). Adipose tissue influences metabolic reprogramming in cancer and was proposed as a contributor to therapy resistance. Using extracellular matrix (ECM)-mimicking hydrogel coculture models of human adipocytes and prostate cancer cells, we show that adipocytes from subcutaneous or bone marrow fat have dissimilar responses under the antiandrogen Enzalutamide. We demonstrate that androgen receptor (AR)-dependent cancer cells (LNCaP) are more influenced by human adipocytes than AR-independent cells (C4-2B), with altered lipid metabolism and adipokine secretion. This response changes under Enzalutamide, with increased AR expression and adipogenic and lipogenic genes in cancer cells and decreased lipid content and gene dysregulation associated with insulin resistance in adipocytes. This is in line with the metabolic syndrome that men with mCRPC under Enzalutamide experience. The all-human, all-3D, models presented here provide a significant advance to dissect the role of fat in therapy response for mCRPC.